Meningkatkan Kemapuan Penalaran Matematis pada Mata Kuliah Statistik melalui Problem Based Learning Berbantuan Aplikasi Teachmint - Arisan Candra Nainggolan; Sondang Noverica Panjaitan (Departement of Mathematics Education, 2024)
Statistics courses are one of the compulsory courses in tertiary institutions and to understand statistical material, mathematical reasoning skills are very necessary. This research aims to test and analyze differences in improving students' mathematical reasoning abilities in statistics courses with Teachmint-assisted Problem Based Learning (PBL) and expository learning. This research uses quantitative methods with a quasi-experimental nonequivalent pretest posttest control-group design. The sample consisted of 70 third semester PGSD students at Santo Thomas Catholic University, Medan. Before and after learning, research data was collected using a mathematical reasoning test consisting of 5 essay questions. Paired sample t-test analysis and independent t-test were used to answer the research hypothesis. The results of the research concluded that students who studied with Problem Based Learning (PBL) assisted by Teachmint achieved a higher increase in mathematical reasoning abilities than those who studied expository, with the criteria for increasing abilities in both classes being in the medium category.